Экономический анализ - Мехович, Сергей Анатольевич; Ершова, Наталья Юрьевна; Минакова, Светлана Михайловна; Дёмочка, Лидия Владиславовна; Ткаченко, Марина Алексеевна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Учебное пособие содержит основные темы экономического анализа с примерами расчетов, что дает возможность изучения фундаментальных понятий теории экономического анализа и их практического применения. Структура учебного пособия позволяет читать английский текст и синхронно видеть русский перевод, что дает возможность иностранному студенту углублять знания русского языка. Учебное пособие также может быть полезным студентам, обучающимся на английском языке.

The textbook contains the main topics of economic analysis with the examples of calculations, which makes possible to study the fundamental concepts of the theory of economic analysis and their practical application. The structure of the textbook allows reading the English text and simultaneously see the Russian translation, which enables a foreign student to deepen the knowledge of the Russian language. The manual can also be useful to students studying in English.
Еconomic аnalysis
Keywords: учебное пособие; экономический анализ; себестоимость продукции; рентабельность; платежеспособность предприятия; textbook; economic analysis; cost price of products; profitability of assets of an enterprise; financial condition and solvency of an enterprise